Тут всё решается методом интервалов
№1. а) x∈(-∞;-2)∪(4;+∞)
б) x∈[0;4]
№2.
а) Надо преобразовать выражение
x²+2x-3
По теореме Виета:
x1+x1=-2
x1*x2=-3
x1=1
x2=-3
x²+2x-3=(x-1)(x+3)
(x-1)(x+3)≤0
x∈[-3;1]
б) x∈(-∞;-2)∪(1;4)
№3.
Тут опять надо преобразовать.
![\frac{2x-3}{1-x} <4\\\frac{2x-3}{1-x}<\frac{4-4x}{1-x} \\\frac{2x-3-4+4x}{1-x}<0\\\frac{6x-7}{1-x} <0\\(6x-7)(1-x)<0 \frac{2x-3}{1-x} <4\\\frac{2x-3}{1-x}<\frac{4-4x}{1-x} \\\frac{2x-3-4+4x}{1-x}<0\\\frac{6x-7}{1-x} <0\\(6x-7)(1-x)<0](https://tex.z-dn.net/?f=%5Cfrac%7B2x-3%7D%7B1-x%7D%20%3C4%5C%5C%5Cfrac%7B2x-3%7D%7B1-x%7D%3C%5Cfrac%7B4-4x%7D%7B1-x%7D%20%5C%5C%5Cfrac%7B2x-3-4%2B4x%7D%7B1-x%7D%3C0%5C%5C%5Cfrac%7B6x-7%7D%7B1-x%7D%20%3C0%5C%5C%286x-7%29%281-x%29%3C0)
x∈(-∞;1)∪(
;+∞)